2021
DOI: 10.2478/jccm-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early versus Delayed Parenteral Nutrition on the Health Outcomes of Critically Ill Adults: A Systematic Review

Abstract: Objectives: This systematic review aims to evaluate and summarise the findings of all relevant studies which identified the effect of early vs delayed parenteral nutrition (PN), early PN vs early supplemental PN and early PN vs standard care for critically ill adults. Methods: The literature search was undertaken using PubMed, Embase, Medline, Clinical Key, and Ovid discovery databases. The reference lists of studies published from 2000 till June 2020 were hand searched. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The findings from previous studies indicate that E-SPN was associated with shorter ICU stay and lower mortality than L-SPN. In parallel to the lower nosocomial infection rate in the E-SPN group, fewer therapeutic antibiotic days were observed in the E-SPN group than in the L-SPN group.…”
Section: Discussionmentioning
confidence: 89%
“…The findings from previous studies indicate that E-SPN was associated with shorter ICU stay and lower mortality than L-SPN. In parallel to the lower nosocomial infection rate in the E-SPN group, fewer therapeutic antibiotic days were observed in the E-SPN group than in the L-SPN group.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, a systematic review and meta‐analysis (SRMA) highlighted that the combined use of EN and PN significantly increased nutrition intake, and was associated with a trend towards improved functional recovery in general patients in the ICU 52 . Nevertheless, due to heterogeneity of studies, the use of SPN remains debatable 40,53 …”
Section: Guidance On Timing and Route Of Mntmentioning
confidence: 99%
“…52 Nevertheless, due to heterogeneity of studies, the use of SPN remains debatable. 40,53 Specific PN concerns for patients receiving ECMO include the potential reaction between the ECMO circuit and the intravenous nutrients. Intravenous lipid emulsions may damage the ECMO circuit, such as breaking of stopcocks, fat emulsion agglutination, clogging of the membrane oxygenator with associated malfunction, and clot-formation within the circuit.…”
Section: The Role Of Pn In Patients Receiving Ecmomentioning
confidence: 99%
“…Some studies support that PN, with close monitoring to avoid overfeeding and hyperglycemia, is beneficial ( 9 , 10 ). A systematic review showed that the supplemental PN patients had shorter ICU stay and lower mortality rates than those on total PN ( 11 ). Current international guidelines recommend the enteral route for ICU patients without contraindications to EN ( 3 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%